Aquifer-wide estimation of longitudinal dispersivity by the combination of empirical equations, inverse solution, and aquifer zoning methods - Mohammad-Mahdi Ansarifar; Meysam Salarijazi; Khalil Ghorbani; Abdol-Reza Kaboli (Applied Water Science, 2022)
Abstract Longitudinal dispersivity is a crucial parameter for the numerical simulation of groundwater quality, which is highly variable. The use of empirical equations and the inverse solution are two main methods of estimating longitudinal dispersivity. This study investigates the estimation of value and aquifer-wide spatial distribution of longitudinal dispersivity parameters using a combination of the empirical equation, the inverse solution method, and the aquifer zoning technique. The combined approach is applied to Bandar-e-Gaz aquifer in northern Iran, and Willmott’s index of agreement was used to assess the simulation precision of total dissolved solids in this aquifer. The values of this criterion were 0.9985–0.9999 and 0.9756–0.9992 in calibration and validation periods showing the developed combined approach obtained high precision for both calibration and validation periods, and the simulation shows remarkable consistency. Also, the one-way sensitivity analysis indicates that the longitudinal dispersivity is more sensitive than the effective porosity in this simulation. The investigation of the spatial distribution of the estimated longitudinal dispersivity by the combined approach indicates that the value of the parameter has a decreasing trend from the south to the north (50–8 m) in the aquifer environment, which is consistent with the changes in the characteristics of porous media in this study area. Therefore, it concludes that the combined approach provides a reliable and appropriate estimation of the spatial distribution of longitudinal dispersivity.